Road safety: A Public Health Perspective - Kansal, Amrita; Lenka, Satya Ranjan (Indian Journal of Community Health, 2015)
Road Traffic Injuries (RTIs) are the eighth leading cause of death globally, and the leading cause of death among young people aged 15–29 years. Current trends suggest that by 2030 road traffic deaths will become the fifth leading cause of death unless urgent action is taken (1). India accounts for about 10% of road crash fatalities worldwide, causing approximately 140,000 deaths and almost a million of serious injuries each year (2). As per the Global Burden of Diseases, Injuries and Risk Factors study- 2010, RTIs are the eighth leading cause of Disability Adjusted Life Years (DALYs) in India. It is significant to note that RTIs were not among the top ten lists of DALYs in India in 1990 and has appeared in 2010 (3).